Climate change impacts on marine water quality: The case study of the Northern Adriatic sea. Issue 2 (30th January 2016) - Rizzi, J.; Torresan, S.; Critto, A.; Zabeo, A.; Brigolin, D.; Carniel, S.; Pastres, R.; Marcomini, A.
Highlights: The proposed methodology analyses climate change impacts on marine water quality. The application to the North Adriatic considers 2 future scenarios: 2070 and 2100. Most of the aquaculture plants are located in areas with high/very high risk scores. RRA outputs provide a basis for the definition of adaptation and management plans. Abstract: Climate change is posing additional pressures on coastal ecosystems due to variations in water biogeochemical and physico-chemical parameters (e.g., pH, salinity) leading to aquatic ecosystem degradation. With the main aim of analyzing the potential impacts of climate change on marine water quality, a Regional Risk Assessment methodology was developed and applied to coastal marine waters of the North Adriatic. It integrates the outputs of regional biogeochemical and physico-chemical models considering future climate change scenarios (i.e., years 2070 and 2100) with site-specific environmental and socio-economic indicators. Results showed that salinity and temperature will be the main drivers of changes, together with macronutrients, especially in the area of the Po' river delta. The final outputs are exposure, susceptibility and risk maps supporting the communication of the potential consequences of climate change on water quality to decision makers and stakeholders and provide a basis for the definition of adaptation and management strategies.